The Impact of Chronic Diseases on Attitudes towards Aging among the Chinese Elderly - Hou Yongmei (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
Background: With the acceleration of the global aging process, how to actively respond to the problem of population aging has attracted increasing attention from the academic community. Previous studies have shown that chronic diseases and attitudes toward aging are two important factors affecting healthy and positive aging. Objective: To understand the prevalence of chronic diseases and attitudes towards aging among the elderly, and to explore the relationship between these two factors. Methods: On the basis of reviewing previous literature, this article clarifies the concepts of aging attitudes and chronic diseases, analyzes the impact of chronic diseases and aging attitudes on the lives and health of the elderly, and based on this, elaborates on the impact of chronic diseases on the aging attitudes of the elderly and its impact pathways. Results: As a result, suffering from chronic diseases has a significant negative impact on the aging attitudes of elderly people. Compared with elderly people who do not suffer from chronic diseases, those who suffer from chronic diseases have a more negative tendency toward aging attitudes. The impact of chronic diseases on attitudes towards aging is mainly achieved through frequent physical pain and discomfort, a significant decline in daily living abilities, increased treatment burden, and misconceptions about the disease. Conclusion: Suffering from chronic diseases is one of the important reasons for elderly people to develop negative attitudes towards aging.